Plasma Menthol Glucuronide as a Biomarker for the Behavioral Effects of Menthol and Nicotine in Humans - Gueorguieva, Ralitza; Schwartz, Elizabeth K. C.; MacLean, R. Ross; DeVito, Elise E.; Eid, Tore; Wu, Ran; O’Malley, Stephanie S.; Sofuoglu, Mehmet (Frontiers in Pharmacology, 2022)
This secondary analysis sought to determine if plasma menthol glucuronide (MG) concentrations predict changes in three outcomes, subjective drug effects, urges to smoke, and heart rate, following concurrent inhaled menthol and intravenous nicotine. A total of 45 menthol and non-menthol cigarettes smokers (36 male, nine female, 20 Black, and 23 White) were included in this double-blind, placebo-controlled study. Across three test sessions, participants were assigned to a different flavor condition for each session: 0% (no menthol), 0.5%, or 3.2% menthol. In each test session, participants received in a random order one intravenous delivery of saline and two intravenous deliveries of nicotine (0.25 mg/70 kg and 0.5 mg/70 kg), each 1 h apart, concurrent with menthol delivery by e-cigarettes. The main outcomes were subjective drug effects, urges to smoke, and heart rate. The results showed that following e-cigarette inhalation, changes in plasma MG concentrations or “menthol boost” increased proportionally to the menthol concentration in the e-liquids. While changes in plasma MG concentrations were not predictive of increases in heart rate or subjective drug effects that are reflective of acute effects from nicotine (i.e., feel good effects, stimulated, aversive effects), they were predictive of cooling effect, a typical effect of menthol, but only in menthol smokers in the absence of concurrent active nicotine infusion. These findings demonstrate the utility of plasma MG as a biomarker both for acute menthol exposure by e-cigarette inhalation and for the examination of the concentration-dependent behavioral and physiological effects of menthol in humans.